The effect of potassium on aluminous phase stability in the lower mantle - Elena-Marie Rogmann; Eleanor S. Jennings; Jennifer Ross; Nobuyoshi Miyajima; Michael J. Walter; Simon C. Kohn; Oliver T. Lord (Contributions to Mineralogy and Petrology, 2024)
The aluminous calcium-ferrite type phase (CF) and new aluminous phase (NAL) are thought to hold the excess alumina produced by the decomposition of garnet in MORB compositions in the lower mantle. The respective stabilities of CF and NAL in the nepheline-spinel binary (NaAlSiO $$_{4}$$ 4 –MgAl $$_{2}$$ 2 O $$_{4}$$ 4 ) are well established. However with the addition of further components the phase relations at lower mantle conditions remain unclear. Here we investigate a range of compositions around the nepheline apex of the nepheline-kalsilite-spinel compositional join (NaAlSiO $$_{4}$$ 4 –KAlSiO $$_{4}$$ 4 –MgAl $$_{2}$$ 2 O $$_{4}$$ 4 ) at 28–78 GPa and 2000 K. Our experiments indicate that even small amounts of a kalsilite (KAlSiO $$_{4}$$ 4 ) component dramatically impact phase relations. We find NAL to be stable up to at least 71 GPa in potassium-bearing compositions. This demonstrates the stabilizing effect of potassium on NAL, because NAL is not observed at pressures above 48 GPa on the nepheline-spinel binary. We also observe a broadening of the CF stability field to incorporate larger amounts of potassium with increasing pressure. For pressures below 50 GPa only minor amounts ( $$<0.011(1)\frac{K}{K+Na+Mg}$$ < 0.011 ( 1 ) K K + N a + M g ) of potassium are soluble in CF, whereas at 68 GPa, we find a solubility in CF of at least $$0.088(3)\frac{K}{K+Na+Mg}$$ 0.088 ( 3 ) K K + N a + M g . This indicates that CF and NAL are suitable hosts of the alkali content of MORB compositions at lower mantle conditions. For sedimentary compositions at lower mantle pressures, we expect K-Hollandite to be stable in addition to CF and NAL for pressures of 28–48 GPa, based on our simplified compositions.